Pengaruh Electronic Word of Mouth (E-WOM) Review Film terhadap Minat Penonton - Insun Asrialdhuha; Rita Gani (UNISBA Press, 2023)
Abstract. Nowadays the era of interactive communication through the development of the internet makes it easy to access information for each individual with the emergence of the concept of Electronic Word of Mouth (E-WOM). E-WOM is a form of conventional communication development, WOM (Word of Mouth). Accessibility is much more effective in making users more active in sharing information such as product/service reviews on social media. TikTok is a social media platform for content production and information providers, one of which is film reviews. E-WOM sources are more trusted by users because they are based on personal experience, are not bound by partners (honest and independent). E-WOM regarding famous film reviews by the TikTok account @kepinhelmy. This study aims to determine whether there is an influence of E-WOM on KKN film reviews in Dancer Village, the @kepinhelmy TikTok account on viewing interest, with three E-WOM dimensions, namely intensity, valence of opinion, and content. This research is classified as a quantitative approach with a positivism paradigm. The data analysis technique uses simple linear regression. Primary data collection was carried out by distributing questionnaires online, and supporting data from literature studies. The results of this study indicate that there is an influence between E-WOM (variable X) on viewing interest (variable Y) with a significant value of 0.699 <0.05 and an R Square gain of 69.9% so that the influence between the two variables is included in the strong category. Abstrak. Dewasa ini era komunikasi interaktif melalui perkembangan internet, memberi kemudahan mengakses informasi bagi tiap individu dengan munculnya konsep Electronic Word of Mouth (E-WOM). E-WOM merupakan bentuk perkembangan komunikasi secara konvensional, WOM (Word of Mouth). Sisi aksebilitas yang jauh lebih efektif menjadikan pengguna lebih aktif dalam membagikan informasi seperti review suatu produk/jasa di media sosial. TikTok salah satu media sosial sebagai wadah produksi sebuah konten dan penyedia informasi, salah satunya ialah mengulas film. Sumber E-WOM lebih dipercayai pengguna karena berdasarkan pengalaman pribadi, tidak terikat mitra (jujur dan independen). E-WOM mengenai review film terkenal oleh akun TikTok @kepinhelmy. Penelitian ini bertujuan untuk mengetahui adakah pengaruh E-WOM review Film KKN di Desa Penari akun TikTok @kepinhelmy terhadap minat menonton, dengan tiga dimensi E-WOM yaitu intensity, valence of opinion, dan content. Penelitian ini diklasifikasikan pendekatan kuantitatif dengan paradigma positivisme. Teknik analisis data menggunakan regresi linier sederhana. Pengumpulan data primer dilakukan dengan menyebarkan kuesioner secara online, dan data pendukung dari studi kepustakaan. Hasil penelitian ini menujukkan bahwa terdapat pengaruh antara E-WOM (variabel X) terhadap minat menonton (variabel Y) dengan nilai signifikan 0.699 < 0,05 dan perolehan R Square 69,9% sehingga pengaruh antara kedua variabel tersebut termasuk dalam kategori kuat.